Freedom To Speech And Expression- A Different Threshold ‘Online’ Vis-à-vis ‘Offline’ Mediums - Chopra , Abhimanyu; Mittal, J.K (International Journal of Psychosocial Rehabilitation, 2020)
-On 24.03.2015 the Hon’ble Supreme Court of India (“SC”) vide its final order and judgment in the Shreya Singhal v. Union of India1 struck down the Section 66A of the Information Technology Act, 2000 (as amended by the Information Technology Amendment Act, 2008) (“Act”)as being contrary to Article 19 and 21 of the Constitution as Section 66A, finding it impossible to save any part of the provision applying the doctrine of severability and declared the provision to be unconstitutional.